Digitization in education system and management of Early Childhood Care Education in Nigeria - Jibola Kadir, Abdullahi Nimota; Abdulganiyu Adebayo, Tijani (Southeast Asia Early Childhood Journal, 2019)
This study investigated digitization in education system and management of early childhood care education in Nigeria. The objectives of this study are to determine the relationship between collaborative learning, game-based learning and management of early childhood care education in North-central, Nigeria. Two hypotheses were formulated and tested. Quantitative research design was used for the study. A self-designed questionnaire titled “Digitization and Management of Early Childhood Care Education Questionnaire” (DMECCEQ) was used to collect information for the study. This study focuses on public primary schools with early childhood care education in North-Central zone, Nigeria. The population of this study comprised all 2,729 head teachers and 5,529 teachers in public primary schools with early childhood care education in North-Central. Sample of 338 head teachers and 361 teachers were proportionally selected in the seven States with the use of Research Advisor (2006) table to determine the sample size of a known population, stratified random sampling technique was used to select primary school head teachers and teachers from the sample schools. This was to ensure that all categories of head teachers and teachers were given equal chance of being selected. The data collected were analyzed using t-test statistical analysis. All hypotheses were tested at the 0.05 level of significance. The result revealed that there was no significant difference between collaborative learning, game-based learning and management of early childhood care education in Nigeria. It was recommended that teachers should continue to make use of collaborative learning in order to increase pupils’ motivation to learn, also make use of appropriate game-based learning for learners to have better self-management, opportunities for collaborative and inquiry-based learning in order to enhance effective management of early childhood care education in Nigeria.